Активний шар тандемного сонячного фотоперетворювача - Бойко, Б. Ю. (ХНУРЕ, 2023)
The photoconverter consists of several layers, of which the active layers are perovskite, a polymer material based on a positively charged polymer and polystyrene sulfonic acid (PEDOT:PSC) and silicon Si. Poly(3,4- ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) is a polymer mixture of two ionomers. One component in this mixture is made up of polystyrene sulfonate which is a sulfonated polystyrene. Part of the sulfonyl groups are deprotonated and carry a negative charge. The other component poly(3,4-ethylenedioxythiophene) (PEDOT) is a conjugated polymer and carries positive charges and is based on polythiophene